Research on Rectifier Load Response Characteristics of MCR-WPT System - HUANG Zhixiong; ZHANG Yitian; LI Zhiyong; CHEN Yougen; WEN Dazhao (Kongzhi Yu Xinxi Jishu)
The relationship between received power and load variation in magnetic coupling resonant wireless power transmission (MCR-WPT) system has received wide attention, and it is strongly correlated with the topology and coupling coefficient. This paper conducts research on the MCR-WPT system with rectifier circuit, and the expression of received power was obtained by establishing the equivalent circuit model of four topologies. Further analysis shows that the load response characteristics of power are significantly affected by the topological structure and coupling coefficient. The maximum power points of the series-series (SS) topology and the parallel-parallel (PP) topology are slightly biased toward the high impedance region. The maximum power point of the series-parallel (SP) topology and the parallel-series (PS) topology are biased toward the low impedance region. Finally, based on the load response characteristics of each topological structure is verified the simulation analysis and experiments, reference suggestions are provided on how the MCR-WPT system should select the topology in different application environments to achieve maximum power transmission.